1987
DOI: 10.1212/wnl.37.4.624
|View full text |Cite
|
Sign up to set email alerts
|

Lack of heart rate changes during an attention‐demanding task after right hemisphere lesions

Abstract: Patients with right hemisphere lesions may be impaired in mobilizing attention and in emotional behavior. If so, autonomic responses to the mobilization of attention should be blunted. This was found when we studied the anticipatory heart rate deceleration that is seen normally in the foreperiod of a warned reaction task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 0 publications
1
36
0
1
Order By: Relevance
“…Both prefrontal and hippocampal lesions abolish the normal P3a increase to the first few novel events. Hippocampal lesions disrupt the P3a and sympathetic skin response (Knight, 1996), and prefrontal lesions reduce the frontal P3a component (Knight, 1984) and the autonomic response to novel stimuli (Yokoyama et al, 1987). Thus, this lesion data and the fMRI results in normals provide converging data on the habituation properties of these regions to novel events.…”
Section: Discussionmentioning
confidence: 55%
“…Both prefrontal and hippocampal lesions abolish the normal P3a increase to the first few novel events. Hippocampal lesions disrupt the P3a and sympathetic skin response (Knight, 1996), and prefrontal lesions reduce the frontal P3a component (Knight, 1984) and the autonomic response to novel stimuli (Yokoyama et al, 1987). Thus, this lesion data and the fMRI results in normals provide converging data on the habituation properties of these regions to novel events.…”
Section: Discussionmentioning
confidence: 55%
“…12 These data suggest that there are differential cerebral effects on autonomic function that depend on the side of the cerebrum. [13][14][15] Results of human insular cortex stimulation suggest rightsided dominance in sympathetic cardiovascular effects and left-sided dominance in parasympathetic effects. 2 In addition, animal experimentation using a rat model with middle cerebral artery occlusion, which results in a consistent lesion of brain including the insular cortex, directly addresses the role of lateralization of brain hemisphere, the site of cerebral infarction, and the effect of age on the ECG perturbations that develop after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent but limited data obtained in patients with cerebral lesions (24,27) suggested that different types of arrhythmias might be the result of right and left hemispheric lesions. These data could explain our observation of different alterations in the spectral parameters in patients with epilepsy with a right or left EEG focus.…”
Section: Discussionmentioning
confidence: 99%